Kesantunan Berbahasa dalam Novel Resign! Karya Almira Bastari - Indah Surya Ningrum; Sri Wahono Saptomo; Titik Sudiatmi (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2022)
The purpose of this study is describe the politeness of language contained in the novel Resign! by Almira Bastari. The method used is descriptive qualitative method. The data used is a piece of dialogue from a character that is suspected to contain compliance and violation of the maxim of politeness in language. The source of data in this study is the dialogue of the characters in the novel. Data collection techniques used are library techniques as basic techniques and reading and note-taking techniques as advanced techniques. The data analysis technique used is descriptive analysis technique. The results showed that there was compliance and violation of the maxim of politeness in the novel Resign!. The politeness maxims found are (1) tact  maxim, (2) generosity maxim, (3) approbation maxim, (4) modesty maxim, (5) agreement maxim, and (6) sympathy maxim. Meanwhile, the violation of the maxim of politeness in the novel Resign! consists of, (1) tact  maxim, (2) generosity maxim, (3) approbation maxim, (4) modesty maxim, and (5) agreement maxim.